Lesbian, Gay, Bisexual & Trans-Sexual: a Christian Ethics Perspective - Tanugraha, Yoas; Amtiran, Abdon A (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes ethical-theological responses to LGBT issues in Protestant context through in-depth study of key Biblical texts and related literature. Using a qualitative approach combining hermeneutical and contextual analysis, this research explores: interpretation of Biblical texts about LGBT, formulation of Christian ethical principles, development of theological-ethical responses, and pastoral care models. Research findings show that Biblical texts consistently and firmly reject LGBT practices as deviation from creation order. The research identifies seven fundamental ethical principles that should underlie church response: principles of creation, holiness, love, redemption, community, human dignity, and pastoral care. In implementation, churches need to develop a